(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
Human rights are rights of a person simply just because they are a human and are inherited by birth. Human rights are inalienable, indivisible and interdependent. To violate human rights of a person simply means to treat that person as not a human being and when respected means that the dignity of all human beings be respected. Although human rights are universally declared and they are protected by international courts and organizations, there are countries globally who are in conflict of granting human rights to their citizens with the clash of cultural relativism. My research is on one country among them which is Qatar and the research work is done on how rights of women in Qatar are exploited, diving deep into the historical context, to understand the legal and social status of women in Qatar, to understand the reforms which have been provided to them in the past years. The ultimate goal to study is to see that human rights of every person is protected and promoted everywhere. Even though there have been several reforms and initiatives taken by the Qatari government, there have still been cases reported by human rights watch and many such international organizations. Laws in Qatar still continue to discriminate against women and lesbian, gay, bisexual, and transgender (LGBT) individuals. Women continued to face discrimination in law and practice. Under the guardianship system, women needed a male guardian’s permission to marry, study abroad on government scholarships, work in many government jobs, travel abroad if aged under 25, and access reproductive healthcare, Women remained inadequately protected in law against domestic violence (Amnesty International, 2024). The supreme political leadership represented by His Highness the Emir and Crown Prince plays an encouraging role in supporting women to achieve equal rights, and improve and enhance women’s position and role in society (Ashghal, n.d.). She has supported the Qatar Institution for Sciences, Education and Society Development that was established in 1996. It is a special institution that first established The Qatar Academy under the chairmanship of Sheikha Al Misnad (Ashghal, n.d.) Her Highness has also shown her interest in helping girls with special needs, by establishing the ’Al Shafallah‘ center, headed by Sheikha Ghalia Bint Mohamed Al Thani (Ashghal, n.d.)